La escritura: ¿espacio liso o estriado? - Freire, HEIKE (Escritura e Imagen, 2005)
From the deleuzian concepts of smooth and fluted space, the author proposes to explore one of the writing origines: the children’s hooks. Gestures without shape or meaning, that affirm the being and make a body with the world, children’s hooks call all senses together in a relational feel and act, previous to any effort of communication. Placed in a zone of indetermination between gesture and pattern or mark, action and representation, figurative art and abstraction, expression and communication, drawing and writing, they ask essential questions about the nature of sensibility and the symbolizing process.